The Cesarean Scar of Pregnancy: Ultrasound Findings and Expectant Management Outcomes - Spong, Catherine Y.; Yule, Casey S.; Fleming, Elaine T.; Lafferty, Ashlyn K.; McIntire, Donald D.; Twickler, Diane M. (American Journal of Perinatology, 2023)
Objective The nomenclature has evolved from low implantation to cesarean scar pregnancy (CSP) and criteria are recommended for identification and management. Management guidelines include pregnancy termination due to life-threatening complications. This article applies ultrasound (US) parameters recommended by the Society for Maternal Fetal Medicine (SMFM) in women who were expectantly managed.Study Design Pregnancies were identified between March 1, 2013 and December 31, 2020. Inclusion criteria were women with CSP or low implantation identified on US. Studies were reviewed for niche, smallest myometrial thickness (SMT), and location of basalis blinded to clinical data. Clinical outcomes, pregnancy outcome, need for intervention, hysterectomy, transfusion, pathologic findings, and morbidities were obtained by chart review.Results Of 101 pregnancies with low implantation, 43 met the SMFM criteria at < 10 weeks and 28 at 10 to 14 weeks. At < 10 weeks, SMFM criteria identified 45out of 76 women; of these 13 required hysterectomy; there were 6 who required hysterectomy but did not meet the SMFM criteria. At 10 to < 14 weeks, SMFM criteria identified 28 out of 42 women; of these 15 required hysterectomy. US parameters yielded significant differences in women requiring hysterectomy, at < 10 weeks and 10 to < 14 weeks' gestational age epochs, but the sensitivity, specificity, positive (PPV), and negative predictive values (NPV) of these US parameters have limitations in identifying invasion to determine management. Of the 101 pregnancies, 46 (46%) failed < 20 weeks, 16 (35%) required medical/surgical management including 6 hysterectomies, and 30 (65%) required no intervention. There were 55 pregnancies (55%) that progressed beyond 20 weeks. Of these, 16 required hysterectomy (29%) while 39 (71%) did not. In the overall cohort of 101, 22 (21.8%) required hysterectomy and an additional16 (15.8%) required some type of intervention, while 66.7% required no intervention.Conclusion SMFM US criteria for CSP have limitations for discerning clinical management due to lack of discriminatory threshold.Key Points
Keywords: cesarean scar pregnancy; low implantation; peripartum hysterectomy ultrasound